Secure and Efficient Data Transmission over Body Sensor and Wireless Networks - Madhur Sikri; Hasan Çam; Narasimha Challa (EURASIP Journal on Wireless Communications and Networking, 2008)
This paper addresses the transmission of medical and context-aware data from mobile patients to healthcare centers over heterogeneous wireless networks. A handheld device, called personal wireless hub (PWH), of each mobile patient first gathers and aggregates the vital sign and context-aware data for various telemedicine applications. PWH transmits the aggregated data to the remote healthcare center over multiple wireless interfaces such as cellular, WLAN, and WiMAX. The aggregated data contain both periodic data and those nonperiodic unpredictable emergency messages that are sporadic and delayintolerant. This paper addresses the problem of providing QoS (e.g., minimum delay, sufficient data rate, acceptable blocking, and/or dropping rate) by designing a packet scheduling and channel/network allocation algorithm over wireless networks. The proposed resource-efficient QoS mechanism is simple and collaborates with an adaptive security algorithm. The QoS and security are achieved mainly with the collaboration of differentiator, delay monitor, data classifier, and scheduler modules within the PWH. This paper also discusses secure data transmission over body sensor networks by introducing key establishment and management algorithms. Simulation results show that the proposed framework achieves low-blocking probability, meets delay requirements, and provides energy-efficient secure communication for the combination of vital signs and context-aware data.